2018
DOI: 10.1634/theoncologist.2018-0334
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Profiling of Parathyroid Carcinoma Reveals Genomic Alterations Suggesting Benefit from Therapy

Abstract: Background Parathyroid carcinoma (PC) is a rare endocrine malignancy that can cause life‐threatening hypercalcemia. We queried whether comprehensive genomic profiling (CGP) of PC might identify genomic alterations (GAs), which would suggest benefit from rationally matched therapeutics. Methods We performed hybrid‐capture‐based CGP to identify GAs and tumor mutational burden (TMB) in tumors from patients with this malignancy. Results There were 85 total GAs in 16 cases (5.3 GAs per case), and the median TMB was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 35 publications
0
32
0
1
Order By: Relevance
“…Targeted next generation sequencing revealed a mutation rate of 7.5% in OSCCs [92]. Novel mutations in PIK3CA were recently reported as candidate driver events in human papillomavirus (HPV)-positive OSCCs [93].…”
Section: Pik3ca Gene Mutations Frequency In Head and Neck Squamous Cementioning
confidence: 99%
“…Targeted next generation sequencing revealed a mutation rate of 7.5% in OSCCs [92]. Novel mutations in PIK3CA were recently reported as candidate driver events in human papillomavirus (HPV)-positive OSCCs [93].…”
Section: Pik3ca Gene Mutations Frequency In Head and Neck Squamous Cementioning
confidence: 99%
“…Recently, PC was linked to immune‐naïve and immune‐tolerant microenvironments, as fewer tumour‐infiltrating lymphocytes (CD3 + and CD8 + ) were found in PC tissue than in atypical adenoma tissue, and increased numbers of tumour‐infiltrating macrophages (CD68 + ) were correlated with the relapse of PC 40 . Although the distribution of immunocytes was not assessed in our present PC cohort, the WGS data provide new evidence supporting the potential involvement of immunoregulation, especially for the wild‐type CDC73 subtype 41 …”
Section: Discussionmentioning
confidence: 63%
“…Going forward, case selection criteria should be defined in detail, and best practices in next generation sequencing (NGS) methodology and interpretation should be followed. Recent studies have suggested that in addition to CDC73, MAPK signaling of the AKT/mTOR/PI3K pathways may be oncogenic pathways (Kasaian et al 2013, Pandya et al 2017, Cui et al 2019, Kang et al 2019. Mutations involving PI3K or TP53 pathways have been reported in about 10-30% of PC in several genomic profiling studies in PC (Yu et al 2015, Pandya et al 2017.…”
Section: Emerging Therapiesmentioning
confidence: 99%
“…Recurrent genetic alterations in other genes such as AKAP9, ZEB1, KDM5C, ADCK1, and PRUNE2 have been reported. Mutations in NF1, SDHA, FAT3, TNRC6A, PTEN, KDR, TERT promoter, DICER1, TSC1 and TSC2 have also been found (Yu et al 2015, Pandya et al 2017, Kang et al 2019, as has amplification and overexpression of the cyclin D1 gene CCND1 (Vasef et al 1999, Zhao et al 2014, Pandya et al 2017 are common in parathyroid carcinoma. A number of these genes, but not all, can potentially be targeted by newer or emerging therapeutic agents.…”
Section: Emerging Therapiesmentioning
confidence: 99%